VIRTUAL LABORATORY WITH CIRCUIT WIZARD TO SUPPORT REMOTE PRACTICE IN ELECTRO LABORATORY - Nurul Syamsiah (Universitas Muhammadiyah Tangerang, 2021)
The Covid-19 pandemic has changed the way people live in interacting and socializing. This is one of the external factors that has a big impact on the learning process, especially practical learning at the National Cyber and Crypto Polytechnic. Practical activities in the electrical laboratory cannot be carried out offline, resulting in cadets experiencing difficulties in understanding and implementing the theories that have been obtained in class, for this reason the tendency to use online technology in practicum activities is getting bigger, one of which is by using virtual laboratories based on face-to-face online by utilizing applications Circuit Wizard practicum. Circuit Wizard is a virtual laboratory practicum application that functions for the analysis, design and measurement of electronic circuits, both analog and digital. The online face-to-face media that can be used in applying the virtual laboratory are zoom meeting, google meet or webex. This paper aims to provide an alternative solution by utilizing a virtual-based practicum model that supports the implementation of conventional practicums and supports cadets to conduct remote research experiments. So that it is expected to meet the standards of the vocational-based curriculum with a composition of 60% practicum and 40% theory.